Assessment of The Level of Access to Urban Services by Index Overlay Maps Method (IOM) and Numerical Taxonomy Model (Case study: Counties of Markazi Province) - Najme mostafavi; zohre shahbazi; Mahdi mobaraki (جغرافیا و آمایش شهری منطقه‌ای, 2017)
Whereas the distribution and arrangement of urban services has an effective role in the spatial displacement of the population and social changes, and given that one of the criteria of sustainable development is the social justice, therefore establishing a logical and coordinated link between population distribution and service distribution in order to achieve sustainability seems necessary. The present study evaluates the availability of urban facilities and services in the cities of Markazi province. In this research, utilization of urban services has been measured in four dimensions of enjoyment of educational, communication, medical and cultural services. In order to achieve this, 24 indexes are selected on the basis of the scale of the opinion of experts and professionals and standardized by the standard rating method; then the standardized indicators will be combined and analyzed in two different ways. Then through Analytic Hierarchy Analysis (AHP), the dimensions of utilization of urban services and the variables of each of them were weighted.The scores of enjoyment  of urban services of  the cities of the province were calculated using two methods of Numerical Taxonomy and Index Overlay Maps (IOM). The results were categorized into five categories in terms of access to services. For better understanding, the results are combined in a Geographic Information System (GIS). Examining the results of the cities' access to urban facilities and services shows a slight difference in the rates obtained from both methods. In all, Farahan city is in the first place in both methods and the cities of Arak and Saveh are considered as deprived areas. With numerical taxonomy, Arak city with a developmental level of 0.84 has the lowest degree of development and among homogeneous cities, Khandab city with a developmental level of 0.28, is the most developed city in the province. By IOM method, Arak and Saveh with 13 points has the least developed and Khandab city with the score of 83 has the most development among the homogeneous cities of the province. In general, there is no proper and reasonable correlation between population, services and urban facilities in Central Provinces.